2016
DOI: 10.1038/pr.2016.181
|View full text |Cite
|
Sign up to set email alerts
|

Is the perceived placebo effect comparable between adults and children? A meta-regression analysis

Abstract: Background: A potential larger perceived placebo effect in children compared with adults could influence the detection of the treatment effect and the extrapolation of the treatment benefit from adults to children. This study aims to explore this potential difference, using a meta-epidemiological approach. Methods: A systematic review of the literature was done to identify trials included in meta-analyses evaluating a drug intervention with separate data for adults and children. The standardized mean change an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 63 publications
0
16
1
1
Order By: Relevance
“…A 2013 review indicated only 2.5% of articles discussed placebo response in pediatrics . A meta‐regression analysis showed a difference in placebo response between adults and children for binary outcomes (i.e., percent of responders), but not for continuous outcomes …”
mentioning
confidence: 99%
“…A 2013 review indicated only 2.5% of articles discussed placebo response in pediatrics . A meta‐regression analysis showed a difference in placebo response between adults and children for binary outcomes (i.e., percent of responders), but not for continuous outcomes …”
mentioning
confidence: 99%
“…While in line with older reviews in children 69 , this is in contrast to adult studies that found no significant differences in placebo effect size between depression and anxiety 70 . This contrast is not unique: placebo responses between children and adults differ significantly for binary outcomes across a wide variety of diseases 71 . One explanation might be that children and adolescents with MDD may be more demoralized than patients with anxiety disorders and are therefore more sensitive to changes in hope and favorable meanings 69 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, selective serotonin reuptake inhibitors (SSRIs) and tricylic antidepressants show smaller effect sizes in treating depression in adolescents compared to adults (Hazell et al, 1995;Hazell & Mirzaie, 2013;Locher et al, 2017;Thapar et al, 2012). This may be partly due to a higher placebo response for depression in young people (Janiaud et al, 2017). Third generation antidepressants such as SNRIs and mirtazapine have not shown to be significantly better than placebo Locher et al, 2017).…”
Section: A N U S C R I P T Introductionmentioning
confidence: 99%